Evaluation of sample extraction methods for proteomics analysis of green algae Chlorella vulgaris. Issue 10 (4th April 2016) - Gao, Yan; Lim, Teck Kwang; Lin, Qingsong; Li, Sam Fong Yau
Abstract : Many protein extraction methods have been developed for plant proteome analysis but information is limited on the optimal protein extraction method from algae species. This study evaluated four protein extraction methods, i.e. direct lysis buffer method, TCA‐acetone method, phenol method, and phenol/TCA‐acetone method, using green algae Chlorella vulgaris for proteome analysis. The data presented showed that phenol/TCA‐acetone method was superior to the other three tested methods with regards to shotgun proteomics. Proteins identified using shotgun proteomics were validated using sequential window acquisition of all theoretical fragment‐ion spectra (SWATH) technique. Additionally, SWATH provides protein quantitation information from different methods and protein abundance using different protein extraction methods was evaluated. These results highlight the importance of green algae protein extraction method for subsequent MS analysis and identification.